Local gradient theory for dielectrics : fundamentals and applications - Hrytsyna, Olha; Kondrat, Vasyl (Singapore : Jenny Stanford Publishing, 2019)
This book is devoted to the development of the local gradient theory of dielectrics. It presents a brief description of the known approaches to the construction of generalized (integral- and gradient-type) continuous theories of dielectrics. It describes a new continuum-thermodynamic approach to the construction of nonlinear high-order gradient theory of thermoelastic non-ferromagnetic polarized media. This approach is based on accounting for non-diffusive and non-convective mass fluxes associated with the changes in the material microstructure. Within the linear approximation, the theory has been applied to study transition modes of the formation of near-surface inhomogeneity of coupled fields in solids, disjoining pressure in thin films, etc. The theory describes a number of observable phenomena (including the surface, size, flexoelectric, pyroelectric, and thermopolarization effects in centrosymmetric crystals, the Meads anomaly, the high frequency dispersion of elastic waves, etc.) that cannot be explained within the framework of the classical theory of dielectrics.
1. A Review of the Gradient and Nonlocal Theories of Electrothermoelastic Polarized Media. 2. Thermodynamic Foundations of Local Gradient Electrothermomechanics of Polarized Nonferromagnetic Solids Taking the Local Mass Displacement into Account. 3. Generalized Local Gradient Theories of Dielectrics. 4. Near-Surface Inhomogeneity of Electromechanical Fields. 5. Stationary Harmonic Wave Processes.
OCLC-licensed vendor bibliographic record.
Keywords: Dielectrics; SCIENCE / Nanostructures; SCIENCE / Solid State Physics; SCIENCE / Life Sciences / General